Effect of goal-directed fluid therapy based on plasma colloid osmotic pressure on the postoperative pulmonary complications of older patients undergoing major abdominal surgery - Anqi Feng; Pan Lu; Yanan Yang; Ying Liu; Lei Ma; Jianrui Lv (World Journal of Surgical Oncology, 2023)
Abstract Background As an important component of accelerated rehabilitation surgery, goal-directed fluid therapy (GDT) is one of the optimized fluid therapy strategies and is closely related to perioperative complications and mortality. This article aimed to study the effect of combining plasma colloid osmotic pressure (COP) with stroke volume variation (SVV) as a target for intraoperative GDT for postoperative pulmonary complications in older patients undergoing major abdominal surgery. Methods In this study, older patients (n = 100) undergoing radical resection of gastroenteric tumors were randomized to three groups: Group C (n1 = 31) received a conventional infusion regimen, Group S1 (n2 = 34) received GDT based on SVV, and Group S2 (n3 = 35) received GDT based on SVV and COP. The results were recorded, including the lung injury score (LIS); PaO2/FiO2 ratio; lactic acid value at the times of beginning (T0) and 1 h (T1), 2 h (T2), and 3 h (T3) after liquid infusion in the operation room; the total liquid infusion volume; infusion volumes of crystalline and colloidal liquids; urine production rate; pulmonary complications 7 days after surgery; and the severity grading of postoperative pulmonary complications. Results The patients in the S2 group had fewer postoperative pulmonary complications than those in the C group (P < 0.05) and the proportion of pulmonary complications of grade 1 and higher than grade 2 in S2 group was significantly lower than that in C group (P <0.05); the patients in the S2 group had a higher PaO2/FiO2 ratio than those in the C group (P < 0.05), lower LIS than those in the S1 and C groups (P < 0.05), less total liquid infusion than those in the C group (P < 0.05), and more colloidal fluid infusion than those in the S1 and C groups (P < 0.05). Conclusion The findings of our study show that intraoperative GDT based on COP and SVV can reduce the incidence of pulmonary complications and conducive to shortening the hospital stay in older patients after gastrointestinal surgery. Trial registration Chinese Clinical Trial. no. ChiCTR2100045671. Registry at www.chictr.org.cn on April 20, 2021.